PENGARUH KEADILAN DISTRIBUTIF, PROSEDURAL DAN INTERAKSIONAL TERHADAP CUSTOMER RETENTION PADA PENGGUNA PRODUK PT TELEKOMUNIKASI INDONESIA TBK DI KOTA BANDA ACEH - Aulia Maulidan; Ahmad Nizam (Departemen Manajemen, 2020)
ABSTRACT: The purpose of this research is to determine The Effect of Distributive Justice, Procedural and Interactional on Customer Retention of PT Telekomunikasi Indonesia product users in Banda Aceh. The sampling technique used in this research is Purposive Sampling, with a sample size of 112 respondents. Equipment for data collection in this study using a questionnaire distributed by Google From. This study used Multiple Linear Regression method to analyse the effect of all the variables involved. Regression results indicate that Distributive, Interactional and procedural Justice have a significant effect on Customer Retention,